(untitled) (Al-Academy, 2026)
The Hijazi Rawashin in the (Jeddah Al-Balad) area possess a rich heritage abundant in geometric details. They consist of a collection of geometric lines, decorative formations, and archaeological engravings with distinct aesthetic characteristics. These creations are the fruit of the efforts of successive artists and craftsmen in the city of Jeddah, resulting from diverse artistic and artisanal expertise. Consequently, these motifs have been employed in modern buildings, utilizing the Hijazi Roshan not merely as a functional architectural element, but as an aesthetic visual text carrying deep semiotic (sign) connotations that reflect the culture of the society in Hijazi architecture. Based on the above, this research aims to study and analyze these motifs, extract the aesthetic and symbolic values of the Roshan, and re-employ and abstract them to beautify the facades of contemporary buildings. This creates an aesthetic language and dialogue between Arab authenticity and contemporary modernity. The research relied on the descriptive-analytical approach to read and analyze the Hijazi Roshan semiotically, and the applied approach to propose strategies for its modern employment in contemporary buildings, aiming to sustain the local identity in a contemporary language compatible with modern construction technologies